2021
DOI: 10.1111/hsc.13627
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition of socioeconomic inequality in COVID‐19 mortality in Iran: A retrospective cohort study

Abstract: This study aimed to investigate the relationship between socioeconomic status and COVID‐19 mortality in Iran. We performed a retrospective cohort study on data from the hospitalised COVID‐19 patients in Qazvin. We collected data on education, self‐reported socioeconomic status, and location of residence as a proxy for socioeconomic status (SES). We applied the Blinder‐Oaxaca decomposition approach to assess the role of socioeconomic inequality in COVID‐19 mortality and determine the main contributors to the ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…During the first emergence of the COVID-19 pandemic, the mortality rate among all hospitalized patients and particularly critically ill patients was pretty high [ 3–5 ]. Age, male gender, co-exciting disorders and lower socioeconomic status have already been identified as the factors associated with higher COVID-19 mortality in this period [ 6 , 7 ]. Multiple studies have shown considerable improvement in the survival of these patients after the first disease surge [ 8–10 ].…”
Section: Introductionmentioning
confidence: 99%
“…During the first emergence of the COVID-19 pandemic, the mortality rate among all hospitalized patients and particularly critically ill patients was pretty high [ 3–5 ]. Age, male gender, co-exciting disorders and lower socioeconomic status have already been identified as the factors associated with higher COVID-19 mortality in this period [ 6 , 7 ]. Multiple studies have shown considerable improvement in the survival of these patients after the first disease surge [ 8–10 ].…”
Section: Introductionmentioning
confidence: 99%
“…This database covers demographic, epidemiological, and clinical characteristics of patients hospitalized due to COVID-19. Please see [ 23 , 24 ] for more detailed information about this database.…”
Section: Methodsmentioning
confidence: 99%